Ensuring Acceptability and Feasibility: The Challenges of Educational Policy Reform in Malaysia. Issue 2 (3rd April 2023) - Bush, Tony; Ng, Ashley Yoon Mooi; Too, Wei Keong; Glover, Derek; Chay, Josephine
ABSTRACT: This article reports research on the implementation of the Malaysia Education Blueprint, 2013–2025, drawing on 49 extended interviews with senior policy makers at federal, state and district levels, and school principals, informed by a systematic review of international and Malaysian literature. The findings show that the reforms are poorly understood by officials and school leaders, leading to partial and unenthusiastic enactment. The paper concludes that such ambitious reforms need to be acceptable, to ensure "ownership" of the reform agenda, and feasible, to avoid disenchantment by officials, school leaders and teachers.